Repositioning of Tak-475 In Mevalonate Kinase Disease: Translating Theory Into Practice. - Marcuzzi, Annalisa; Loganes, Claudia; Celeghini, Claudio; Kleiner, Giulio (Curr Med Chem, 2018)
BACKGROUND: Mevalonate Kinase Deficiency (MKD, OMIM #610377) is a rare autosomal recessive metabolic and inflammatory disease. In MKD, defective function of the enzyme mevalonate kinase, due to a mutation in the MVK gene, leads to the shortage of mevalonate- derived intermediates, which results in unbalanced prenylation of proteins and altered metabolism of sterols. These defects lead to a complex multisystem inflammatory and metabolic syndrome. OBJECTIVE: Although biologic therapies aimed at blocking the inflammatory cytokine interleukin- 1 can significantly reduce inflammation, they cannot completely control the clinical symptoms that affect the nervous system. For this reason, MKD can still be considered an orphan drug disease. The availability of MKD models reproducing the MKD-systematic inflammation, is crucial to improve the knowledge on its pathogenesis, which is still unknown. New therapies are also required in order to improve pateints' conditions and their quality of life. METHODS: MKD-cellular models can be obtained by biochemical inhibition of mevalonatederived isoprenoids. Of note, these cells present an exaggerated response to inflammatory stimuli that can be reduced by treatment with zaragozic acid, an inhibitor of squalene synthase, thus increasing the availability of isoprenoids intermediates upstream the enzymatic block. RESULTS: A similar action might be obtained by lapaquistat acetate (TAK-475, Takeda), a drug that underwent extensive clinical trials as a cholesterol lowering agent 10 years ago, with a good safety profile. CONCLUSIONS: Here we describe the preclinical evidence supporting the possible repositioning of TAK-475 from its originally intended use to the treatment of MKD and discuss its potential to modulate the mevalonate pathway in inflammatory diseases.
Keywords: Acyl Coenzyme A; Cholesterol; Drug Repositioning; Farnesyl-Diphosphate Farnesyltransferase; Humans; Hypercholesterolemia; Mevalonate Kinase Deficiency; Oxazepines; Phosphotransferases (Alcohol Group Acceptor); Piperidines